Kedudukan Pesantren dalam Sistem Hukum Nasional: Perspektif Pancasila dan Penguatan Ekonomi Umat - Aisha Salsabila; Raisa Diaz Aisya; Nurul Aeni; Febriana Nurrahmania F; Alif Khomsani Margi Utami (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
Islamic boarding schools play a strategic role in national development, not only as religious educational institutions, but also as agents of social and economic empowerment for the people. Law No. 18 of 2019 strengthens their position in the national legal system, in line with the values of Pancasila, which emphasizes social justice and respect for diversity. This study aims to analyze the position of Islamic boarding schools within the national legal framework, emphasizing the relevance of Pancasila and their contribution to strengthening the economy of the Muslim community. The method used is a qualitative approach with normative-legal literature study and qualitative analysis of regulations, literature, and practices of economic empowerment in Islamic boarding schools. The results of the study show that Islamic boarding schools have legal legitimacy as independent institutions in education, da'wah, and community empowerment, while also playing a role in developing cooperatives, micro-enterprises, and santri-based entrepreneurship. Thus, Islamic boarding schools have proven to be important actors in strengthening the economy of the Muslim community and implementing the Pancasila value of social justice.